1995
DOI: 10.1021/bi00009a023
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Methylation and Acetylation of Arginine-Rich Histones in Cycling and Arrested HeLa Cells

Abstract: In the following report the relationship between histone methylation and histone acetylation has been examined in HeLa cells to better define the distribution of these two modifications. By labeling methylated histones in the presence or absence of sodium butyrate, we have found that the methylation of H3 is much more targeted to rapidly acetylated chromatin than is the methylation of H4, which largely involves the unacetylated subtype even in the presence of butyrate. Newly methylated H3 is highly likely to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
0
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 42 publications
3
37
0
2
Order By: Relevance
“…5). However, radiolabeling studies (6,7) and genetic experiments in yeast (8,9) show acetylation is highly dynamic and heterogeneous, with different populations of histones characterized by distinct rates of acetylation and deacetylation (5,10). We have shown that all detectable K4-trimethylated histone H3 (H3K4me3) across murine nuclei, irrespective of location or association, is subject to dynamic acetylation at multiple lysine residues, becoming maximally acetylated within 10-30 min of treatment with trichostatin A (TSA) (11).…”
mentioning
confidence: 99%
“…5). However, radiolabeling studies (6,7) and genetic experiments in yeast (8,9) show acetylation is highly dynamic and heterogeneous, with different populations of histones characterized by distinct rates of acetylation and deacetylation (5,10). We have shown that all detectable K4-trimethylated histone H3 (H3K4me3) across murine nuclei, irrespective of location or association, is subject to dynamic acetylation at multiple lysine residues, becoming maximally acetylated within 10-30 min of treatment with trichostatin A (TSA) (11).…”
mentioning
confidence: 99%
“…One of the first histone modifications to be identified nearly forty-five years ago was the methylation of histone H4 lysine 20 (H4K20) 4 (2). Earlier biochemical studies linked H4K20 methylation to diverse biological events including transcriptional regulation, chromatin compaction, cell division, and the formation of heterochromatin (3)(4)(5)(6)(7)(8)(9). Importantly, it was also found that H4K20 is differentially methylated in vivo and therefore can be either mono-, di-, or trimethylated (10).…”
mentioning
confidence: 99%
“…Par exemple, l'acétylation de la lysine 16 de H4 en concomitance avec la phosphorylation de la sérine 10 de H3 amplifie l'activité transcriptionnelle du chromosome X masculin [17]. De même, H3 et H4 sont des cibles privilégiées pour la méthylation lorsqu'elles sont acétylées [22]. Enfin, des modifications post-traductionnelles de même nature peuvent entraîner des effets opposés.…”
Section: La Particule Coeur De Nucléosomeunclassified
“…Des études récentes montrent que la structure des NCP n'est pas figée et qu'il est possible d'observer, notamment in vitro, des mouvements rapides d'ouverture et de fermeture de L'ADN nucléosomal par FRET (fluorescence resonance energy transfer) ou FCS (fluorescence correlation spectroscopy) [20][21][22]. Les nucléosomes restent bien enroulés pendant 250 ms puis l'ADN s'ouvre pendant des intervalles de temps variant de 10 à 50 ms, assez longs pour rendre l'ADN accessible à des protéines et à des enzymes [24].…”
Section: Ouverture Spontanée De L'adn Nucléosomal : « Respiration » Dunclassified